2017
DOI: 10.1016/j.cub.2017.09.007
|View full text |Cite
|
Sign up to set email alerts
|

Long-Fiber Carbon Nanotubes Replicate Asbestos-Induced Mesothelioma with Disruption of the Tumor Suppressor Gene Cdkn2a ( Ink4a/Arf )

Abstract: SummaryMesothelioma is a fatal tumor of the pleura and is strongly associated with asbestos exposure. The molecular mechanisms underlying the long latency period of mesothelioma and driving carcinogenesis are unknown. Moreover, late diagnosis means that mesothelioma research is commonly focused on end-stage disease. Although disruption of the CDKN2A (INK4A/ARF) locus has been reported in end-stage disease, information is lacking on the status of this key tumor suppressor gene in pleural lesions preceding mesot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
117
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(123 citation statements)
references
References 40 publications
3
117
1
2
Order By: Relevance
“…The early genetic event at the Cdkn2a locus by exposure to either long asbestos or long carbon nanotubes was the hypermethylation of Cdkn2a , whereas deletion of Cdkn2a occurs at a late stage of the malignant transformation 40 . The homozygous deletion of Cdkn2a/2b was not observed in the epithelioid subtype (EM) (0/6), but it was observed in the sarcomatoid subtype (SM) (4/5) in our study 36 and EM (1/5) in another study 41 when iron saccharate was used for rat MM carcinogenesis.…”
Section: Discussioncontrasting
confidence: 51%
“…The early genetic event at the Cdkn2a locus by exposure to either long asbestos or long carbon nanotubes was the hypermethylation of Cdkn2a , whereas deletion of Cdkn2a occurs at a late stage of the malignant transformation 40 . The homozygous deletion of Cdkn2a/2b was not observed in the epithelioid subtype (EM) (0/6), but it was observed in the sarcomatoid subtype (SM) (4/5) in our study 36 and EM (1/5) in another study 41 when iron saccharate was used for rat MM carcinogenesis.…”
Section: Discussioncontrasting
confidence: 51%
“…Another example of a potentially dangerous material are the carbon nanotubes (CNTs), a novel industrial material with many applications. The genetic alterations provoked by these nanotubes in rat malignant mesothelioma were similar to those induced by asbestos [39].…”
Section: Sepiolite Interacts With the Dna By Causing Double-strand Brmentioning
confidence: 68%
“…Recent investigations have revealed that depletion of p19 (ARF) and epigenetic silencing of p16 with CDKN2A hypermethylation are frequently associated with mesothelioma progression due to either amosite asbestos or long-shaped CNTs exposure. 3 Mechanistically, the degree of genotoxic oxidative stress measured by 8-OHdG and the activation of pro-oncogenic signal pathways regulated by Akt, ERK1/2, and Src kinase are quite similar in the pleura between asbestos and CNTs exposure. This fact is consistent with Dr Fukushima's review article 1 stating that exposure to MWCNTs results in asbestos-like pathologic alterations including lung carcinoma and pleural mesothelioma.…”
Section: Dear Editormentioning
confidence: 98%
“…Importantly, malignant mesothelioma is considered to be a "disease of gene loss" rather than being associated with driver mutations. 3 Genetic analyses have clarified the depletions and/or loss-of-functional mutations of CDKN2A, NF2, BAP1 genes, and both p53-dependent DNA repair pathway and PI3K/Akt/mTOR signal transduction are involved in mesothelioma development. Alterations in CDKN2A locus with inactivation of p16 (INK4a) are reported in more than a half of malignant mesothelioma patients.…”
Section: Dear Editormentioning
confidence: 99%
See 1 more Smart Citation